A Rushed Quality - Odell, David (punctum books, 2015)
These fragments collected here (in 2 books, "A Rushed Quality" and "Bodying Forth") belong neither to philosophy nor to poetry - and yet they are for the most part focused on a substantial area of overlap between these two venerable disciplines, vis-à-vis the question, "What is it like to be X?" Philosophers like to fill in the X with something exotic like a bat or a dolphin, or even an Artificial Intelligence, while poets tend to fill it with something else, equally exotic, namely themselves. For the diffident and introspective author of A Rushed Quality and Bodying Forth, the X, while definitely human, is perhaps someone in general, equally distant from and equally intimate with both the writer and the reader in the very moment of their eponymous activity. The start of it all was the perception of what was called the "rushed quality," as something persistent and bothersome and of which there was no question of its ever being shed. Rather than evaded or denied, it was welcomed because it seemed for the first time since childhood to mark a structural occurrence presenting a new metaphysical datum. As it happened, this quality proved very elusive in its mature bothersomeness and the inquiry into it soon turned into a sort of quasi-theoretical fascination, which took as its main theme the fate of pure subjectivity - the utterly unfunctional, utterly useless, utterly dispensible feeling of being. The rushed quality is perhaps merely the sense of it draining away, or its long-sustained decrescendo.